Perancangan dan Pengembangan Perangkat Lunak “Alat Bantu Pengambilan Keputusan Investasi dan Kredit“ (Studi Kasus KPRI UNS, BNI 46, BRI Cabang Surakarta) - Eko Liquiddanu; Rahmaniyah Dwi Astuti (Performa: Media Ilmiah Teknik Industri, 2002)
This paper proposes a decision making software for customer to get information about monthly cost include credit interest and installment. This software can complete decision making tools in Industrial Engineering laboratory. This research is established with system planning and modelling. Finally, it can be concluded that credit and investment analysis software is very useful to solve engineering economic problem.